Utility and ruin probability relationship through premium equivalence - Mamplata, Jonathan B.; Escaner, Jose Maria L. (Quezon City Institute of Mathematics, College of Science, University of the Philippines Diliman, 2013)
Utility is a satisfaction received from consuming a commodity or service. Ruin probability is the probability that an insurer's surplus will fall below zero for a certain period of time. Many researches focused on the pricing insurance premium using the concept of utility functions. Also some focused on finding the probability that the company or insurer will be insolvent at any given point in time via the ruin probability. This thesis focused mainly on the calculation of the insurance premium by setting a tolerance level for the ruin probability. After the premium was solved, the corresponding utility will be determined. It was assumed that the loss or claims amount follows an exponential distribution or geometric distribution. A closed for expression for the finite-time ruin probability will be determined. This closed form expression will be used to generate algorithm that calculated the corresponding ruin probability. Computer program will be constructed for these calculations using Scilab.
Thesis (M.S. Applied Mathematics)--University of the Philippines Diliman
Keywords: Probabilities; Insurance premiums